Comparing Adult Learning Systems: an emerging political economy. (8th May 2013) - Rees, Gareth
<x xml:space="preserve">Abstract</x> Adult learning systems have come to be dominated by the view that the essential role of adult learning is to generate the high levels of skills deemed necessary for competitiveness and growth in the globalised economy. This 'education gospel' is underpinned by human capital theory (HCT) and its contemporary conceptualisation in terms of the knowledge‐based economy. Nevertheless, it remains the case that there are significant differences in the strategies of national governments towards adult learning and in patterns of engagement with the learning opportunities that are made available. This paper sets out to explore how this diversity in national systems of adult learning might be addressed analytically. Adult learning is embedded in characteristic regimes of economic and social institutions, which can be understood in terms of a systematic international political economy. In particular, adult learning systems are explored by reference to the models of capitalist organisation elaborated in the neo‐institutionalist analysis of 'varieties of capitalism' (Hall and Soskice, 2001): the liberal market economy and the co‐ordinated market economy. A major alternative is provided by Esping‐Anderson's (1990; 1999) analysis of 'welfare state regimes'. Moreover, Rubenson and Desjardins (2009) have used this theoretical framework as a means of analysing systematic variations between national adult learning systems. These analyses raise questions about the use of national states as the key unit of analysis. Significant divergences in institutional arrangements and access to opportunities for adult learning (by social group or locality, for example) may be obscured by this method of comparative analysis. Moreover, consideration of the micro‐theoretical foundations of these approaches highlights the difficulties in moving beyond the economistic 'rationality' of HCT. The issue here is the extent to which norms of behaviour in relation to engaging in adult learning can be appropriately understood in terms of a relatively homogeneous, national social system, rather than in terms of a much more socially differentiated repertoire of norm‐based orientations.